Comparative Analysis of Interactive Web Services - Stančić, Hrvoje; Crnec, Dina; Mateljan, Stjepan Salopek, Anita; Sanković, Dijana (2007)
The fact that interactive web services have entered all spheres of life motivated the authors to investigate how this new collaborative media influences modern information society. The paper discusses the results obtained by comparative analysis of different collaborative media. Interactivity was considered as one of the most important criteria for choosing between the many different inter¬ active web services. The authors analyzed the main characteristics of the cho¬ sen services, classified them into groups and compared them within those groups. The paper stresses the importance of today’ s most popular services, varying from search engines, all kinds of online communities, different types of leisure services to e-learning services, on the behavior and expectations of all participants in the global Internet-based communication. Search engines were analyzed according to ranking and credibility while Web community services were analyzed according to many of their interactive and communication pos¬ sibilities. The category of leisure services ranged from those services created for leisure time to those created for other purposes but used as leisure ser¬ vices. Also, the interactive services of the largest Croatian e-learning solution, implemented at the Faculty of Humanities and Social Sciences at the Univer¬ sity of Zagreb, were analyzed. The positive and negative sides of each of the analyzed groups of interactive web services were compared and synthesized, and their effects on media de¬ velopment and the society in general were analyzed. In the paper, the authors tried to emphasize the great social aspect of the Internet today and the services it provides. They showed how society has a great influence on the growth of the Internet, but also how the Internet has an even greater effect on the rela¬ tionships and activities within society. Thus, this paper does not only give an overview of the comparative analysis of interactive web services but also shows the mutual influence of the collaborative media and human creativity on the development of the information society.
Projekt MZOS
ENG